Vulnerabilities and resiliency of the coastal people in the Bangladesh : a sociological study of Satkhira coastal areas - Mustari, Sohela (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study aims at investigating the household experiences of the people in southwestern coastal areas of Bangladesh, mainly in a village called Napitkhali. Based on empirical data collected at the village level, the research analyzes their vulnerabilities and resilient capacities against several natural disasters. By employing Risk Society Theory (RST) of Ulrich Beck (1992), the analysis developed mostly three main thematic experiences. These are vulnerability, resiliency, and finally focusing on the difference in the level of vulnerability and resiliency. From the methodological point of view, the study relied heavily on qualitative methods for collecting data. In addition, a small survey was conducted to provide the demographic information, making the study holistic in nature. The findings focused on different major sub-themes related to vulnerabilities due to natural disasters by revealing that these vulnerabilities are manifested centrally under livelihood options and other social necessities of everyday life. In the later section, it shows that despite facing continuous vulnerabilities, the villagers have the capacities to get rid of them through finding proper alternatives. The last part of the research findings exposes that both vulnerability and resilient strategies are embedded by the socio-demographic factors which are significant in creating differences in the level of vulnerability and resiliency of the villagers. The discussion part of the thesis primarily reveals that the RST of Ulrich Beck is mostly true for these villagers of Napitkhali. However, the theory is modified slightly as the discussion establishes that both the vulnerabilities and the alternative mechanisms are dynamic processes for these villagers based on their socio-demographic characteristics.